Basic formal education quality, information technology and inclusive human development in Sub-Saharan Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2018)
This study assesses the relevance of basic formal education in information technology for inclusive human development in 49 countries in sub-Saharan Africa for the period 2000-2012. The question it aims to answer is the following: what is the relevance of basic formal education in the effect of mobile phone penetration on inclusive human development in sub- Saharan Africa when initial levels of inclusive human development are taken into account? The empirical evidence is based on instrumental quantile regressions. Poor primary education dampens the positive effect of mobile phone penetration on inclusive human development. This main finding should be understood in the perspective that, the education quality indicator represents a policy syndrome because of the way it is computed, notably: the ratio of pupils to teachers. Hence, an increasing ratio indicates decreasing quality of education. It follows that decreasing quality of education dampens the positive effect of mobile phone on inclusive development. This tendency is consistent throughout the conditional distribution of inclusive human development. Policy implications for sustainable development are discussed.
Keywords: G20; I10; I32; O40; O55; 330; Quality education; Mobile phones; Inclusive human development; Sustainable Development; Africa